GENERAL UNDERSTANDING OF INTERROGATIVE WORDS IN ARABIC (British Journal of Global Ecology and Sustainable Development, 2023)
Before delving into the specifics, it is essential to annotate the importance of interrogative words in language. They enable effective communication by allowing individuals to seek clarification, request information, and engage in meaningful conversations. Understanding interrogative words in Arabic can be particularly helpful for language learners, translators, and anyone interested in the intricacies of this language.